(3faGFS GdYfGUQ deLGdS Gdedc GdfGUQs - (3CHh SGde GdfUjHj , eMeO Hf WdMg Hf eMeO Hf GdMSf GdbQTj, ceGd GdOjf CHh SGde,J (B652 (3g` s ((3eMeO Hf TcQ GdeGdcj s)
(3ChdgG (B:s
(3hHYO, aEf Chdi eG JWdYJ Edjg CacGQ Gdedhc hdeG cGfJ GdfXQGJ GdcQjeI s
(3BNQgG (B:s
(3hJeGe ebGeGJg, hSJQI gahGJg, hecaQI SjFGJg, ceG Cfg fUQI bSeGJg, hZQI SeGJg s
(3HgG fXGe GdJYbjHIs
(3UaMI GdYfhGf eRhbI hGdfSNI ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B175s
Keywords: (3GdCOHs